2009
DOI: 10.1186/1756-0500-2-217
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila KDM2 is a H3K4me3 demethylase regulating nucleolar organization

Abstract: BackgroundCG11033 (dKDM2) is the Drosophila homolog of the gene KDM2B. dKDM2 has been known to possess histone lysine demethylase activity towards H3K36me2 in cell lines and it regulates H2A ubiquitination. The human homolog of the gene has dual activity towards H3K36me2 as well as H3K4me3, and plays an important role in cellular senescence.FindingsWe have used transgenic flies bearing an RNAi construct for the dKDM2 gene. The knockdown of dKDM2 gene was performed by crossing UAS-RNAi-dKDM2 flies with actin-Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 11 publications
5
30
0
Order By: Relevance
“…We can see that two h3k4me3s occur in all those 4 patterns, which indicates that the h3k4me3 has a positive impact on the gene expression. This is confirmed by the biological observations: h3k4me3 is an important epigenetic landmark for active transcription [15] [12].…”
Section: Gene Activitysupporting
confidence: 86%
“…We can see that two h3k4me3s occur in all those 4 patterns, which indicates that the h3k4me3 has a positive impact on the gene expression. This is confirmed by the biological observations: h3k4me3 is an important epigenetic landmark for active transcription [15] [12].…”
Section: Gene Activitysupporting
confidence: 86%
“…In agreement with our data, Frescas et al also observed H3K4me3 demethylase activity for Fbxl10 (12). This is further supported by a very recent publication analyzing the demethylase function of the Drosophila homolog dKdm2 which was described as a H3K4me3 demethylase in vivo (30). Nevertheless, it has to be considered that histone demethylases act in multienzyme complexes, and the specificity of histone modifiers may be dependent on interaction with other proteins or modifications on histone residues nearby (1,5).…”
Section: Discussionmentioning
confidence: 53%
“…The Drosophila KDM2 (dKDM2) is the single homolog of the mammalian KDM2A and KDM2B (Fig. 1A) (Dui et al, 2012; Jin et al, 2004; Kavi and Birchler, 2009; Lagarou et al, 2008). Biochemical purification for dRING-associated proteins coupled with mass spectrometric analysis led to the identification of dKDM2 as a component of dRING-associated factors complex (dRAF), a Polycomb group (PcG) silencing complex composed of dRING, Posterior Sex Comb (PSC) and dKDM2 (Lagarou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of KDM2B was also shown to significantly reduce H2A ubiquitination in mouse embryonic stem cells (Wu et al, 2013). However, knocking down dKDM2 in vivo using actin5C-Gal4 to drive the expression of dKdm2-dsRNA in the third instar larvae did not reveal any effects of dKDM2 depletion on the levels of H3K36me2, H3K9me2, and H3K4me2 assayed by Western blot and immunofluoresence staining; instead, a strong increase of H3K4me3 was observed, suggesting that dKDM2 specifically demethylates H3K4me3 in vivo (Kavi and Birchler, 2009). In addition, depletion of dKDM2 in salivary glands resulted in multiple nucleoli (Kavi and Birchler, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation